1994
DOI: 10.1002/maco.19940450207
|View full text |Cite
|
Sign up to set email alerts
|

Mikrobielle Werkstoffzerstörung – Simulation, Schadensfälle und Gegenmaßnahmen für anorganische nichtmetallische Werkstoffe: Biodeteriorationsprozesse an anorganischen Werkstoffen und mögliche Gegenmaßnahmen

Abstract: Biodeteriorationsprozesse an anorganischen Werkstoffen wie Naturstein, Beton oder Glas können in ihren Schädigungsweisen nach biogeochemischen und biogeophysikalischen Mechanismen unterteilt werden. Im Zusammenhang mit der partiellen Ätzung und Lösung von Bestandteilen, hervorgerufen durch die biogene Freisetzung anorganischer bzw. organischer Säuren (Biokorrosion) sowie der biogenen Oxidation mineralbildender Kationen (Biooxidation), kommt es zur Schwächung, des Gefüges im jeweiligen Werkstoff. Durch den Aufw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that certain bacteria, fungi and algae are able to colonize facades, roof tiles, building stone, concrete and even glass (Bock andSand 1993, Warscheid andBraams 2000). These organisms not only produce optical disturbances; due to the release of organic and inorganic acids, they also cause serious damage (Warscheid and Krumbein 1994). The latter has been estimated at 2-4 billion € per year in Germany alone (Flemming 1995).…”
Section: From Plant Leaves To Technical Surfacesmentioning
confidence: 99%
“…Numerous studies have shown that certain bacteria, fungi and algae are able to colonize facades, roof tiles, building stone, concrete and even glass (Bock andSand 1993, Warscheid andBraams 2000). These organisms not only produce optical disturbances; due to the release of organic and inorganic acids, they also cause serious damage (Warscheid and Krumbein 1994). The latter has been estimated at 2-4 billion € per year in Germany alone (Flemming 1995).…”
Section: From Plant Leaves To Technical Surfacesmentioning
confidence: 99%